Melampaui Fasilitas: Modal Simbolik dan Intensi Kunjungan Peziarah ke Makam Syekh Anom Sidakarsa, Jawa - Farihatul Fitriyah; Siti Prihatiningtyas (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2026)
This study examines how symbolic capital shapes pilgrims’ visiting intention at a Javanese religious heritage site. While tourism studies commonly emphasize material components such as amenities and infrastructure, pilgrimage destinations often operate through spiritual authority and sacred narratives. Using a qualitative case study of the Tomb of Syekh Anom Sidakarsa in Kebumen, Central Java, data were collected through field observations, semi-structured interviews with caretakers, pilgrims, local vendors, and community leaders, and document analysis. The findings show that pilgrims’ visiting intention is primarily driven by symbolic capital associated with the saintly figure of Syekh Anom Sidakarsa, including narratives of sanctity, genealogical legitimacy, and beliefs in spiritual blessings. Material factors such as amenities and accessibility function mainly as supporting conditions for visitor comfort, while ancillary services remain limited. By integrating the 4A tourism framework with Bourdieu’s concept of symbolic capital, this study offers a sociological perspective on pilgrimage tourism and provides insights for managing sacred heritage destinations